Beyond the Rainbow: On Rural Queer Rhetoric - Fallon, Courtney Danielle, author; Gibson, Katie L., advisor; Claycomb, Ryan M., committee member; Dunn, Thomas R., committee member; Williams, Elizabeth A., committee member (Colorado State University. Libraries, 2026)
This dissertation introduces rural queer rhetoric as a framework that elucidates place and class as critical animators of gender, sexuality, and race in contemporary Western LGBTQ+ subject formation. By examining Chappell Roan’s rural queer celebrity persona, rural trans folks’ speeches in conservative U.S. state legislatures, and a rural LGBTQ+ campout’s organizational rhetoric, I identify emergent worldmaking tactics that disrupt metronormative logics embedded in mainstream U.S. culture and politics. My dissertation proffers rural queer rhetoric as a theoretically valuable site of academic inquiry and provides case studies of worldmaking praxis as models for everyday application. I examine how Chappell Roan performs worldmaking through her critical performance of self as placed rural queer bricolage, how transgender rhetors in rural U.S. state governments enact worldmaking as placed political praxis through liminal performance, and how participants at an annual campout hosted by a localized LGBTQ+ advocacy organization in a rural U.S. state engage in worldmaking with/against/despite the organization’s placemaking rhetorics. Through both queer rhetorical criticism and participatory critical rhetoric approaches, this project contributes to scholarly conversations on intersectional inquiry, worldmaking, and place in research through its introduction of rural queer rhetoric as a significant site of meaning-making that both exposes the ways contemporary neoliberal Western LGBTQ+ identity politics enable totalizing metronormative logics and illuminates the possibilities and limitations of rural imaginaries in their capacity to facilitate queer struggle.
Keywords: Performance; Rhetoric; Worldmaking; Place; LGBTQ+ politics; Rural queerness